2016
DOI: 10.1007/s12291-016-0625-2
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte Membrane Bound ATPase and Antioxidant Enzyme Changes Associated with Vascular Calcification is Reduced by Sodium Thiosulfate

Abstract: Sodium thiosulfate (STS), a cyanide antidote has been reported to possess antioxidant and calcium chelation effects, useful for the treatment of renal failure due to vascular calcification and urolithiasis. The present study investigated the in vivo modulatory effects of STS on erythrocyte calcium, phosphorous levels, lipid peroxidation, antioxidant enzyme and membrane ATPase activities (Ca, NaK, Mg and 5'' nucleotidase) in an adenine induced model of vascular calcification in rats. Adenine (0.75%) was supplem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…Erythrocytes are considered the major target of free radicals because their high polyunsaturated fatty acids (PUFAs) content, such as linoleic acid and arachidonic acid [ 49 , 50 ]. In our study we showed that rats treated with ethanol showed marked higher erythrocytes ROS such as H 2 O 2 , hydroxyl radical and superoxide anion levels than all groups.…”
Section: Discussionmentioning
confidence: 99%
“…Erythrocytes are considered the major target of free radicals because their high polyunsaturated fatty acids (PUFAs) content, such as linoleic acid and arachidonic acid [ 49 , 50 ]. In our study we showed that rats treated with ethanol showed marked higher erythrocytes ROS such as H 2 O 2 , hydroxyl radical and superoxide anion levels than all groups.…”
Section: Discussionmentioning
confidence: 99%
“…Several hypotheses have been proposed regarding the mechanisms by which sodium thiosulfate improves calciphylaxis. According to a recent report [6], sodium thiosulfate possesses antioxidant activity and improves endothelial cell function. As a result, vasodilation occurs and blood flow is increased, which promotes healing of ulceration.…”
Section: Case Descriptionmentioning
confidence: 99%